Thermodynamics Studies of a Novel Calix [4] Arene Derivative Designed to Bind Herbicides (Global Journal of Science Frontier Research, 2015)
Abstract not found
Keywords: Calix[4]arene receptor; Detection of herbicides; 1H NMR investigations; Conductance measurements; Thermodynamics parameters of complexation